The Relationship Between Bilingualism and Achievement - Marwa Elkhouly (2025)
This paper addresses the cognitive and academic impacts of bilingualism, particularly focusing on students in the UAE, where bilingual education programs have been significantly promoted. Bilingual students are hypothesized to have enhanced executive control and cognitive flexibility, potentially leading to superior academic performance compared to monolingual peers. Empirical evidence and theoretical frameworks such as Krashen’s Second Language Acquisition Theory and various cognitive development theories are explored to understand how bilingualism may affect academic achievement. The study utilizes a mixed-method approach, employing interviews and questionnaires among educators in UAE schools to gauge perceptions and real-world impacts of bilingual education on student achievement. Findings are expected to contribute to the ongoing debate regarding the efficacy of bilingual education programs and provide insights into optimal instructional strategies in bilingual settings.